2016
DOI: 10.1093/jjco/hyw172
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective observational study of occult cervical lymph-node metastasis in T1N0 tongue cancer

Abstract: Patients with tumors ≥2 mm in thickness or muscle invasion developed neck metastasis, suggesting that elective neck dissection may be warranted for patients with these findings. For preoperative assessment of the need for elective neck dissection, magnetic resonance imaging would be a potential modality for T1N0 tongue cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…A large number of authors have reported that early stage node-negative OSCC developing regional metastasis has a poor prognosis [ 3 , 13 , 25 ]. There are two options for treatment of the neck in clinically node-negative OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of authors have reported that early stage node-negative OSCC developing regional metastasis has a poor prognosis [ 3 , 13 , 25 ]. There are two options for treatment of the neck in clinically node-negative OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…High correlation has been reported of tumour measurements between MRI and pathology in literatures (Geol et al., 2016; Imai et al., 2017; Jung et al., 2009; Kwon et al., 2016; Lam et al., 2004; Preda et al., 2006). The difference of values measured between the two methods needs to be evaluated.…”
Section: Introductionmentioning
confidence: 93%
“…However, the reported occult metastasis rate varies based on race and geographical differences (4)(5)(6)(7), and a few authors have noted that a wait-and-see policy does not compromise survival (4,5). Further, the shoulder pain and dysfunction associated with neck dissection, although uncommon, should not be neglected (8).…”
Section: Introductionmentioning
confidence: 99%